The Level of Self-Esteem and Attitudes Toward Science Among Student Teachers in Palestinian Universities Name - Haneen Majed Jamel Yaser Taqatqa; Belal Ahmad Mohamad Abu Eideh (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study investigated science student teachers' self-esteem and their attitudes toward teaching science. Additionally, it explored the correlations between student teachers' self-esteem and various variables, such as gender, specialization, and accumulative average. Methods: The descriptive methodology was employed, and data was collected from a stratified random sample of 469 student teachers, completing their third and fourth academic years in science programs during the academic years 2020/2021. Two tools, a self-esteem scale and the attitudes toward science questionnaire, were used for data collection. Results: The findings indicated that student teachers' self-esteem and attitudes toward teaching science were moderate. Significant differences were observed in self-esteem and attitudes based on gender, accumulative average, and educational qualification. However, no significant differences were found based on the field of specialty. A significant correlational relationship between student teachers' self-esteem and attitudes toward teaching science was also established. Conclusions: The study highlights the importance of incorporating self-esteem into the professional standards for new science teachers and emphasizes the need to focus on educationally qualified graduates in science faculties who aspire to become science teachers.